Effects of alloy compositions on hydrogen behaviors at a nickel grain boundary and a coherent twin boundary. (1st April 2020) - Hui, Jun; Yang, Guo; Liu, Min; Liu, Wenguan; Wang, Biao
Abstract: The effects of several common metallic and nonmetal alloy compositions (i.e., Cr, Mo, B, and P) on the energetics and kinetics of hydrogen behaviors at a nickel grain boundary (GB) and a coherent twin boundary (CTB) were systematically investigated by first-principles calculations. H, Cr, Mo, B, and P have a stronger segregation into Ni GB than Ni CTB due to the presence of a cavity in GB. Cr, Mo, B, and P all act as obstacles for H segregation and diffusion in both GB and CTB, but the physical mechanisms are different: In Ni GB, Cr and Mo result in the shrinkage of isosurfaces of optimal charge densities for H, and B and P provide a strong competitive tendency to accumulate into the GB; in Ni CTB, Cr and Mo induce charge accumulation, and B and P result in a repulsive interaction to H. The present study provides the microscopic images of H compositions in Ni GB and CTB under the effects of alloy compositions; this is essential for understanding the mechanism of hydrogen embrittlement (HE) and improving the ability of alloys against HE. Highlights: Effects of common elements on H were studied by first-principles calculations. Both Ni grain boundary (GB) and coherent twin boundary (CTB) were studied. Effects of alloying elements on energetics and kinetics of H were studied. The effects were decomposed into physical and chemical components. The mechanisms at electronic and atomic levels were explored.